Measurement of intellectual capital of Lithuanian cities by a composite index - Krušinskas, Rytis; Bruneckienė, Jurgita (Journal of Business Economics and Management, 2014)
The article comprises analysis of theoretical and practical aspects of measurement of the city's intellectual capital. This article includes analysis of the intellectual capital concept and possibilities of its application at the city level, generalization of the organization intellectual capital models and principles, which, considering the macro-level context and overview of tendencies of economic growth, are applied for measurement of intellectual capital of the city. The newly created city's intellectual capital balance index is presented. The empirical application of the method proved that it is an appropriate tool for the measurement of the city's intellectual capital within a country, which corresponds to the second level NUTS of the European Union. This article is one of the ambitions to promote the methodological background for urban governance and improvement of intellectual capital as well as competitiveness of Lithuanian cities. The city's intellectual capital balance index can be used as the tool for assessment of efficiency and timeliness of the urban and national development strategies, also as the tool for publicity for innovation, creativity and “smartness” of the city or the whole country.